Importance of cerebrospinal fluid analysis in the era of McDonald 2010 criteria: a German-Austrian retrospective multicenter study in patients with a clinically isolated syndrome - Huss, André Michael; Halbgebauer, Steffen; Oeckl, Patrick; Trebst, Corinna; Spreer, Annette; Borisow, Nadja; Harrer, Andrea; Brecht, Isabel Valeska; Balint, Bettina; Stich, Oliver; Schlegel, Sabine; Retzlaff, Nele; et al. (Journal of neurology, 2016)
The majority of patients presenting with a first clinical symptom suggestive of multiple sclerosis (MS) do not fulfill the MRI criteria for dissemination in space and time according to the 2010 revision of the McDonald diagnostic criteria for MS and are thus classified as clinically isolated syndrome (CIS). To re-evaluate the utility of cerebrospinal fluid (CSF) analysis in the context of the revised McDonald criteria from 2010, we conducted a retrospective multicenter study aimed at determining the prevalence and predictive value of oligoclonal IgG bands (OCBs) in patients with CIS. Patients were recruited from ten specialized MS centers in Germany and Austria. We collected data from 406 patients; at disease onset, 44/406 (11 %) fulfilled the McDonald 2010 criteria for MS. Intrathecal IgG OCBs were detected in 310/362 (86 %) of CIS patients. Those patients were twice as likely to convert to MS according to McDonald 2010 criteria as OCB-negative individuals (hazard ratio = 2.1, p = 0.0014) and in a shorter time period of 25 months (95 % CI 21-34) compared to 47 months in OCB-negative individuals (95 % CI 36-85). In patients without brain lesions at first attack and presence of intrathecal OCBs (30/44), conversion rate to MS was 60 % (18/30), whereas it was only 21 % (3/14) in those without OCBs. Our data confirm that in patients with CIS the risk of conversion to MS substantially increases if OCBs are present at onset. CSF analysis definitely helps to evaluate the prognosis in patients who do not have MS according to the revised McDonald criteria.